Consequences of exposure of operating room students to clinical learning challenges - mostafa Roshanzadeh; Ali Taj; Shirmohammad Davoodvand; Somayeh Mohammadi (Zanjan University of Medical Sciences and Health Services, 2024)
Background & Objective: Clinical environment is a significant component in relation to students' learning. Exposure to the challenges of the clinical learning environment has some consequences for students and can affect their learning. Identifying these consequences will moderate the challenges, and therefore, improve the quality of learning in such environments. The present study aimed to explain the consequences of exposure to clinical learning challenges among operating room students. Materials & Methods: This study was conducted based on the qualitative content analysis approach at Shahrekord University of Medical Sciences, Shahrekord, Iran, in 2022. A total of 14 surgical technology students were selected by a purposeful sampling method. The required data were collected using in-depth, semi-structured face-to-face interviews. The data were analyzed using Graneheim and Lundman's approach. Results: The results of the study revealed two categories (i.e., learning distress and using harmful clinical shortcuts) and four subcategories (i.e., feeling of helplessness in learning, anxiety, incomplete care, and wrong modeling). Under the conditions and challenges in the learning environment, students felt helpless toward learning, experienced anxiety, and suffered from learning distress. It was also found that in the clinical learning atmosphere, when faced with the existing challenges, the students would be likely to facilitate the care process and attempt to do unprincipled care by imitating the wrong personnel examples. Conclusion: Faced with the learning challenges of the clinical environment, the operating room students suffered from learning stress and resorted to harmful clinical shortcuts. Examining students' anxiety and their disappointment and helplessness toward the conditions and challenges of clinical education, identifying clinical wrong patterns in the care process, as well as modifying the care process provided by the personnel as wrong role models of students can have an effective impact in reducing the existing consequences.